THE FREQUENCY OF HELICOBACTER PYLORI INFECTION IN CIRRHOTIC GASTROPATHY - Sebati ÖZDEMİR and Hakan ŞENTÜRK and Nagehan SEZGİÇ and Abdullah SONSUZ and Gülşen ÖZBAY and Ayhan YÜCEL and Perihan AKIN and Muzaffer GÜRAKAR (Turkish Journal of Gastroenterology, 2020)
-